The Effect of Aloe Vera Extract to Extensive Lesion and Expression of Transforming Growth Factor (TGF-β) on Alkaline Chemical Trauma Cornea Model - Fahcreza; Elsa Iskandar; Rachmat Hidayat; Petty Purwanita; Anang Tribowo; Riani Erna (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2018)
Abstract Background: Chemical trauma to the cornea is an emergency condition of the eye that requires early diagnosis and good treatment. Alkaline have ability to saponify fatty acids in cells and cell membranes which can make penetration into the stroma and destroy proteoglycans and collagen in cells. Aloe vera (AV) contains several active substances that are reported to have anti-inflammatory, immunomodulatory, and wound healing effects. AV has been reported to accelerate the healing process of corneal epithelial defects by increasing fibroblast proliferation, collagen production and growth factor production. This study aims to determine the difference between the effect of aloe vera extract with a concentration of 10%, 20%, 40% and BSS on the healing of extensive corneal lesions in white wistar rats alkaline trauma models. Method: This study was an experimental study with a pre and posttest only with control group design in vivo approach to 30 Wistar white rats which were divided into 5 treatment groups for 3 days. Comparative analysis of effectiveness using the ANNOVA test or the Kruskal Wallis test and continued by the post hoc test. Results: Based on the one way ANOVA test there was a statistically significant difference in effectiveness between the five treatment groups on the percentage of corneal wound healing area and TGF-β expression with an assessment of p = 0,000 each. The administration of alloevera (AV) concentration of 20% had a significant difference in percentage of healing of corneal lesions and TGF-β expression compared with other treatment groups with p = 0,000 each. Large differences in the area of corneal lesions in the 40% AV group were -0.45 in the BBS group, 0.146 in the 10% AV group, 0.493 in the 20% AV group. The difference in the AV group 10% was 0.30 in the BBS group, -064 in the AV group 20%, and -0.14 in the AV group 40%. However, TGFβ expression in the normal control group that did not receive treatment was 54.94 (53.21-56-12). TGFβ levels in the BSS group were 10.44, the 10% aloe vera group was 25.43, 47.99 for the 20% aloe vera group and 37.95 for the 40% aloe vera group. Conclusion: There is a difference between the effect of aloe vera extract with concentrations of 10%, 20%, 40% and BSS on the extensive healing of corneal lesions in white wistar rats with alkaline chemical trauma models.